Telaah Kritis Pelayanan Umum di Perkotaan - Ratminto Ratminto (Magister Ilmu Administrasi Publik, 2004)
This article discusses about various important aspects of public services, particularly in the urban areas. The author critically analyses the quality of public services provided by municipality government from various aspects. On the basis of his analysis, the author argues that accountability, responsibility, accessibility and efficieng are among other important indicators which should be applied to measure the qual0ty of public services.